2017
DOI: 10.1016/j.lindif.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics between student vs. teacher perceptions of mathematics task-orientation and mathematics performance among adolescents

Abstract: This study examined the dynamics between perceptions of mathematics task-orientation and mathematics performance among Finnish adolescents over a period of two last years of secondary school. Task-orientation in math was assessed at the beginning of grade 8 and again at the end of grade 9 using both student and teacher-reports. At the same time points, students' mathematics performance was evaluated via standardized test. The cross-lagged associations of task-orientation and mathematics performance were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Along with literacy skills, motivation plays a role in successful mathematics learning onwards from early years (Fitzpatrick & Pagani 2013). Previous research has shown that children's task orientation (for an in-depth presentation on the concept of task orientation, see Björn, Räikkönen, Aunola & Kyttälä 2017) is an important factor that explains mathematics performance (Aunola, Leskinen & Nurmi 2006). As one of the learning orientation domains, task orientation describes positive concentration ability and willingness, as well as engagement in a given task.…”
Section: Introductionmentioning
confidence: 99%
“…Along with literacy skills, motivation plays a role in successful mathematics learning onwards from early years (Fitzpatrick & Pagani 2013). Previous research has shown that children's task orientation (for an in-depth presentation on the concept of task orientation, see Björn, Räikkönen, Aunola & Kyttälä 2017) is an important factor that explains mathematics performance (Aunola, Leskinen & Nurmi 2006). As one of the learning orientation domains, task orientation describes positive concentration ability and willingness, as well as engagement in a given task.…”
Section: Introductionmentioning
confidence: 99%
“…Анализ последних исследований и публикаций, в которых рассматривались аспекты этой проблемы и на которых обосновывается автор; выделение неразрешенных раньше частей общей проблемы. Сегодня научным сообществом активно изучаются вопросы влияния восприятия преподавателем своих студентов на их образовательные результаты [1] (выявлено, что убеждение учителя в необходимости наличия таланта для успешного обучения математике влияет на успешность освоения программы в начальной школе [2]), наличия искажающих факторов при оценке успеваемости обучающихся [3,4], влияния отношений между учениками и учителем на их успеваемость [5], наличия взаимосвязи между самооценкой учениками своих знаний и результатами выполнения задач по математике [6], зависимости между настроением учеников на занятиях и энтузиазмом преподавателя [7,8], отличия в восприятии когнитивных проблем учениками и учителями [9].…”
unclassified
“…Also, evidence suggests that girls tend to be less confident in their mathematical skills and score higher on mathematical anxiety measures (Dowker et al, 2016). On the other hand, no gender differences were found between Finish adolescent boys' and girls' self-reported task orientation in mathematics, which was defined as focus on the task and persistence (Björn, Räikkönen, Aunola, & Kyttälä, 2017). Although these previous studies did not specifically focus on task beliefs in mathematics, the inconsistent results on gender differences make it worthwhile to investigate gender differences in task beliefs about the ENL and voluntary ENL use.…”
Section: Gender Differences In Mathematicsmentioning
confidence: 95%